Tuberculosis of Waldeyer’s Ring with an Atypical Presentation as Chronic Adeno-Tonsilitis - Kamath, Panduranga M (J Clin Diagn Res, 2015)
Primary tuberculosis of the oropharynx and nasopharynx is a rare clinical entity.It usually arises secondary to pulmonary tuberculosis. We report a rare case of a 20-year-female, who presented with fever and throat pain. Examination revealed hypertrophied adenoids and tonsils, which was ultimately proved as tuberculosis.Enlargement of the palatine tonsils could be due to a multitude of causes, and a thorough evaluation is necessary to arrive at the right diagnosis.Increased awareness of nasopharyngeal and oropharyngeal tuberculosis is important in tropical countries, as the disease may be overlooked resulting in inappropriate management.